Relationships between coach's leadership, group cohesion, affective states, sport satisfaction and goal attainment in competitive settings - González-García, Higinio; Martinent, Guillaume; Nicolas, Michel (SAGE Publications Inc, 2022)
We examined whether a perceived coach's leadership predicted group cohesion and whether group cohesion predicted intensity and direction of positive affect and negative affect experienced during competition, sport satisfaction and goal attainment following the completion of a sports competition. A sample of 296 competitive athletes (Mage = 21.61; standard deviation = 6.32) participated in the study and completed a series of self-report questionnaires assessing the aforementioned constructs. A partial least square path modelling approach was used to examine the relationships between the study variables. Results of the structural partial least square path modelling model revealed that: (a) democratic coach behaviour negatively predicted Group Integration Task, (b) authoritarian coach positively predicted Individual Attractions to the Group-Social, and (c) reward positively predicted Group Integration Task. Moreover, partial least square path modelling results also revealed that (a) Individual Attraction to the Group-Task positively predicted the direction of negative affect during competition, (b) authoritarian coach marginally positively predicted Group Social Integration during competition, and (c) Group Social Integration marginally negatively predicted the direction of Negative Affects during competition. Thus, contradicting previous studies, results did not provide evidence of the empowering effect of democratic coach leadership on Group Integration Task. Finally, results provided evidence for the significant relationships between group cohesion and athletes’ competitive outcomes such as affective states experienced during competition.
Keywords: achievement; motivation; team sport; Scopus; JCR